ATP-Sensitive Potassium Channel Activation Induces Angiogenesis In Vitro and In Vivo - Umaru, Bukar; Pyriochou, Anastasia; Kotsikoris, Vasileios; Papapetropoulos, Andreas; Topouzis, Stavros (The Journal of pharmacology and experimental therapeutics, 2015)
Intense research is conducted to identify new molecular mechanisms of angiogenesis. Previous studies have shown that the angiogenic effects of hydrogen sulfide (H2S) depend on the activation of ATP-sensitive potassium channels (KATP) and that C-type natriuretic peptide (CNP), which can act through KATP, promotes endothelial cell growth. We therefore investigated whether direct KATP activation induces angiogenic responses and whether it is required for the endothelial responses to CNP or vascular endothelial growth factor (VEGF). Chick chorioallantoic membrane (CAM) angiogenesis was similarly enhanced by the direct KATP channel activator 2-nicotinamidoethyl acetate (SG-209) and by CNP or VEGF. The KATP inhibitors glibenclamide and 5-hydroxydecanoate (5-HD) reduced basal and abolished CNP-induced CAM angiogenesis. In vitro, the direct KATP openers nicorandil and SG-209 and the polypeptides VEGF and CNP increased proliferation and migration in bEnd.3 mouse endothelial cells. In addition, VEGF and CNP induced cord-like formation on Matrigel by human umbilical vein endothelial cells (HUVECs). All these in vitro endothelial responses were effectively abrogated by glibenclamide or 5-HD. In HUVECs, a small-interfering RNA–mediated decrease in the expression of the inwardly rectifying potassium channel (Kir) 6.1 subunit impaired cell migration and network morphogenesis in response to either SG-209 or CNP. We conclude that 1) direct pharmacologic activation of KATP induces angiogenic effects in vitro and in vivo, 2) angiogenic responses to CNP and VEGF depend on KATP activation and require the expression of the Kir6.1 KATP subunit, and 3) KATP activation may underpin angiogenesis to a variety of vasoactive stimuli, including H2S, VEGF, and CNP.